Glibenclamide treatment in a Cantú syndrome patient with a pathogenic ABCC9 gain‐of‐function variant: Initial experience. Issue 8 (7th June 2019) - Ma, Alan; Gurnasinghani, Sunita; Kirk, Edwin P.; McClenaghan, Conor; Singh, Gautam K.; Grange, Dorothy K.; Pandit, Chetan; Zhu, Yung; Roscioli, Tony; Elakis, George; Buckley, Michael; Mehta, Bhavesh; et al.
Abstract: Cantú syndrome (CS), characterized by hypertrichosis, distinctive facial features, and complex cardiovascular abnormalities, is caused by pathogenic variants in ABCC9 and KCNJ8 genes. These genes encode gain‐of‐function mutations in the regulatory (SUR2) and pore‐forming (Kir6.1) subunits of KATP channels, respectively, suggesting that channel‐blocking sulfonylureas could be a viable therapy. Here we report a neonate with CS, carrying a heterozygous ABCC9 variant (c.3347G>A, p.Arg1116His), born prematurely at 32 weeks gestation. Initial echocardiogram revealed a large patent ductus arteriosus (PDA), and high pulmonary pressures with enlarged right ventricle. He initially received surfactant and continuous positive airway pressure ventilation and was invasively ventilated for 4 weeks, until PDA ligation. After surgery, he still had ongoing bilevel positive airway pressure (BiPAP) requirement, but was subsequently weaned to nocturnal BiPAP. He was treated for pulmonary hypertension with Sildenafil, but failed to make further clinical improvement. A therapeutic glibenclamide trial was commenced in week 11 (initial dose of 0.05 mg –1 kg –1 day –1 in two divided doses). After 1 week of treatment, he began to tolerate time off BiPAP when awake, and edema improved. Glibenclamide was well tolerated, and the dose was slowly increased to 0.15 mg −1 kg −1 day −1 over the next 12 weeks. Mild transient hypoglycemia was observed, but there was no cardiovascular dysfunction. Confirmation of therapeutic benefit will require studies of more CS patients but, based on this limited experience, consideration should be given to glibenclamide as CS therapy, although problems associated with prematurity, and complications of hypoglycemia, might limit outcome in critically ill neonates with CS.